Relationship Between Human Resource Assets, Organization, Relational, And Financial Literacy On Optimization Of MSMES (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
MSMEs are experiencing rapid growth along with advances in business and technology, and play a significant role in increasing national income. This study examined 385 MSMEs in Gunung Kidul that had been established for at least one year and utilized financial digitalization through systems and technology. The study results showed that human resources, organizational capital, relational capital, and digital literacy positively influenced MSME performance. However, intellectual capital did not influence MSME performance because if it was not balanced with practical skills, it would not improve performance. This finding confirms that the competitiveness among MSME human resources is increasingly fierce, so optimizing performance depends not only on knowledge or intellectual aspects, but also on skills in establishing relationships and managing organizational resources. This study contributes to resource theory by emphasizing the importance of a combination of digital literacy, organizational capacity, relationships, and human resource quality to encourage sustainability and improve MSME performance in the digital era.
Keywords: Human Resources; Intellectuals; Organization; Relations; Digital Literacy